The Vinaya (Discipline) As the Core of Buddhism for Response to the Social Conflict - Ratthamedho, Phramaha Thanarat (International Journal of Multidisciplinary in Cultures & Religions Studies, 2021)
The present world is obviously made up of complex societies, which have undergone tremendous changes through the ages and this change will continue. The world is shrinking day by day at a faster pace than ever before. Countries do easily get connected through various modes of transport and communication and people get to know any event happening in any corner of the world any time. These changes are not without its problems. Societies have reached an anomic stage that situation has arisen where the norms of society are unclear and no longer applicable to the current conditions leading to an increase in the rate of social conflicts such as Terrorism, Murder, Prostitute, Rape, Corruption, Anti-race, Anti-Religion, Drug, Alcoholism etc. On this connection, in the recent conditions, there are the religious institutions have a lot of effort to manage different aspects of social problem. All emphatic religions are tried to find an answer, for to find out which of these issues. So, when a social conflict has been occurred, the society of human being needs to have regulation for controlling and preserving harmony, which is nothing other than jurisprudence.